Evaluation Of The Population Administration Information System At The Population And Civil Registration Office Of North Bengkulu Regency - Azhary, Hemelda; IS, Tuti Handayani; Imanda , Antonio (Jurnal Multidisiplin, 2025)
This study evaluates the implementation of the Population Administration Information System (SIAK) at the Population and Civil Registration Office (Dukcapil) of North Bengkulu Regency. Using a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation of Dukcapil officers and service users, this study uncovers three main dimensions of evaluation. Process evaluation indicates that SIAK implementation has met national standards with the support of trained human resources and multi-layered data verification, but still faces challenges in internal coordination and limited network infrastructure, particularly in rural areas. Benefit evaluation confirms increased service efficiency, such as a reduction in KTP issuance time from one week to 1–2 days and an acceleration of data verification from three days to four hours thanks to automated validation that reduces administrative errors. However, these benefits are not evenly distributed as some areas with limited internet connections still rely on manual services. Consequence evaluation indicates increased transparency and quality of public services, with the public able to access services more quickly and accurately. However, digital transformation faces challenges in the form of a digital literacy gap and differences in technology adoption rates between generations. The implications of this research emphasize the need for improved network infrastructure, strengthened internal coordination, enhanced human resource capacity, and ongoing technology outreach and mentoring to ensure optimal and equitable implementation of SIAK.